Phenotypic and genotypic characterization of Ornithobacterium rhinotracheale from poultry with respiratory clinical signs in Peru between 2015 and 2017 - Cotaquispe Nalvarte, Rony Yunior (2020)
Ornithobacterium rhinotracheale, like other bacteria associated with respiratory conditions, has been subjected to a demanding selection pressure due to the use of disinfectants and antibiotics, which has been generating resistant multidrug strains, as well as an increase in its genetic variability. The objective of the study was to characterize 36 O. rhinotracheale isolates from poultry from five regions of Peru by a profile of eight antibiotics (fosfomycin, amoxicillin, ciprofloxacin, enrofloxacin, norfloxacin, sulfatrimetropin, doxycycline, oxytetracycline), and genotyping by ERIC-PCR techniques. The results indicate the presence of multidrug resistance of 2 to 6 antibiotics in 94.4% (n = 34) of the strains and 6.6% (n = 2) strains were resistant to 1 antibiotic, being the most common resistance to fosfomycin (77.8 %) and sulfatrimetropin (75.0%). At least, 11 differentiated genetic profiles (A-K) were found, being the most frequent the D profile in the isolates (55.6%). The results suggest the presence of O. rhinotracheale strains with moderate variability and antibiotic resistance profiles fosfomycin and sulfatrimetropin.